(3TQM JgPjH GdcdGe hGdefWbs - (3GdUOjbj, GdOhGfj, LdGd GdOjf, eMeO Hf CSYO J (B918 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; JgPjH GdefWb hGdcdGe JhTjMI HPcQ GdeaVd GdefYGe CeG HYO agPg YLGdI fGaYI HefWb GdJgPjH GdPj gh GdYde aj QTGbI GdJQJjHs
(3BNQgG (B:s
(3bhdg Ch hLO GdhGMO abW eY GdecGf GdZjQ cGJSei GdeNJUQ GaQGOg aj gPg GdTeS GdeTGgOIs
(3QSGdI Ydi gGeT cJGH JgPjH GdefWb ddJaJRGfj GdefShNI YGe (B1081 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 32s
(3eYLe GdeDdajf (B3 / 126s
(3cTa GdXfhf (B1 / 515 - 516s
(3TPQGJ GdPgH (B8 / 160s
Keywords: (3GdadSaI hGdefWbs